OP75 Increased Consumption of Fruit and Vegetables for the Primary Prevention of Cardiovascular Diseases – A Cochrane Systematic Review. (10th September 2013) - Hartley, L C; Igbinedion, E; Holmes, J; Thorogood, M; Clarke, A; Stranges, S; Hooper, L; Rees, K
Abstract : Background: Cardiovascular disease (CVD) is a global burden and varies between regions. This regional variation has been linked in part to dietary factors and low fruit and vegetable intake has been associated with higher rates of CVD. Objectives: To determine the effectiveness of advice to increase fruit and vegetable consumption and the provision of fruit and vegetables to increase consumption, for the primary prevention of CVD. Methods: The following electronic databases were searched with no language restrictions from their inception to October 2012: MEDLINE, EMBASE, CINAHL, Web of Science, the Cochrane Library and trial registers. Included studies fulfilled the following criteria: study design – RCT's, participants - free of CVD (includes those at high risk of CVD), intervention - advice to increase fruit and vegetable consumption or the provision of fruit and vegetables to increase consumption, comparator - no intervention or minimal intervention (e.g. no face to face advice), outcomes - diagnosis of CVD or change in the risk factor profile for CVD (blood pressure, lipids). Two reviewers independently screened titles and abstracts, assessed shortlisted studies for formal inclusion/exclusion, abstracted data and assessed methodological quality. Results: Database searching resulted in 7222 of which 298 went forward for informal inclusion and exclusion. Nine RCT's met the inclusion criteria. Five trials investigated the provision of fruit and vegetables, and four trials examined advice to increase fruit and vegetable consumption. The intervention components, and the dietary advice provided differed between trials. None of the trials reported clinical events. There was no strong evidence for effects of individual trials of provision of fruit and vegetables on cardiovascular risk factors, but trials were heterogeneous and short term. Dietary advice showed favourable effects on blood pressure (SBP: mean difference -3.0 mmHg [95% CI -4.91, -1.08], DBP: mean difference -0.85 mmHg [-1.96, 0.26]) and to a lesser extent total cholesterol levels over six months (mean difference -0.13 mmol/l [-0.33, 0.08]), but few trials contributed to each analysis. Conclusion: There are very few studies to date examining provision of, or advice to increase the consumption of, fruit and vegetables in the absence of additional dietary interventions or other lifestyle interventions for the primary prevention of CVD. The limited evidence suggests advice to increase fruit and vegetables as a single intervention has favourable effects on CVD risk factors but more trials are needed to confirm this.